State-owned enterprises and threats to national security under investment treaties - MCLAUGHLIN, Mark (Institutional Knowledge at Singapore Management University, 2020)
The internationalization of investment by State-owned enterprises is driving the evolution of foreign investment regulation throughout the Western world. National security lies at the heart of host State concerns, yet the contours of the concept remain indistinct. Consequently, State-owned enterprises are subject to differential legal standards that can be vague and ambiguous. This article considers whether, and under what circumstances, host State security measures targeting State-owned enterprises comply with obligations under investment treaties. Provision for pre-establishment national treatment and security exceptions will be crucial in balancing the autonomy afforded to host States to protect their national security, and guarding State-owned enterprises against protectionist or discriminatory measures.